Discriminatory Analysis to Predict Tax Aggressiveness Categories Based on Return on Asset and Debt to Equity Ratio in Agricultural Sector Companies on the IDX - Dwi Selvianti; F Fauziyah; Imarotus Suaidah (LP2M IAIN Palopo, 2026)
The purpose of this research is to test the ability of ROA and DER in distinguishing companies that implement tax aggressiveness strategies and companies that do not implement tax aggressiveness strategies. This study uses discriminatory analysis techniques as the main method wazith 8 samples of agricultural sector companies listed on the IDX in the 2021-2024 period. The sample used is grouped based on the median value of the Effective Tax Rate of 0.23. The results showed that, partially the Return on Asset variable was significant in distinguishing the two groups (Sig. 0.021) and the Debt to Equity Ratio variable was partially insignificant in distinguishing the two groups (Sig. 0.101). Simultaneously, the ROA and DER were proven to be able to form a significant discriminant function (Sig. 0.037) with a classification accuracy rate (Hit Ratio) of 71.9%. Research provides empirical contribution to the literature on the distinguishing factors of the characteristics of tax aggressiveness in the agricultural sector. Practically, this finding has implications for the Directorate General of Taxes as a reference for taxpayer analysis through increasing the focus of supervision on companies that have high profitability due to the tendency to carry out tax aggressive practices.